Valiant one [videorecording (DVD)] - Myrick, Daniel, 1962-; Tipton, Eric; Barnett, Steve (Film producer); Strokes, Chase; Condor, Lana; Borges, Desmin (Briarcliff Entertainment, 2025)
In the heart-pounding military thriller Valiant One, a routine mission spirals into a fight for survival when a US Army helicopter crashes deep within North Korean territory. With their communications equipment destroyed, Captain Edward Brockman an Specialist Selby must lead the team through hostile terrain, cut off from Us military support as they attempt a daring escape across the treacherous Demilitarized Zone.